An array receiver scheme for reducing refraction induced artifacts in ultrasonic tof tomography - SRINVASA RAO, K.; SRINVASAN, T. M. (Archives of Acoustics, 1987)
Different types of errors caused by refraction effects in ultrasonic time-of-flight (TOF) tomography are discussed. The effectiveness of a three element experimental array receiver in reducing refraction induced artifacts in ultrasonic TOF tomography is evaluated. During data acquisition, TOF and peak values of the received signal is measured for each of the three receivers. A peak value index (PVI) is computed for each receiver. The PVIs give an indication of the deviation of the interrogating beam from line-of-sight path. Based on these indices a propagation path is assumed for the ultrasonic beam in the medium and image reconstruction is performed along these assumed propagation paths. These propagation paths are closer to the actual paths than the generally assumed line-of-sight paths and hence superior tomograms are obtained when reconstruction is done along these assumed propagation paths. Tomograms of agar gel objects and excited sheep heart indicate that this method is effective in reducing the geometric distortions in the reconstructions. The tomograms are quantitatively evaluated using two error measures.